Flow analysis of a front opening unified pod (FOUP) subjected to different fan filter unit (FFU) coverage area in mini-environment. (November 2021) - Lin, Tee; Zargar, Omid Ali; Lee, Tzu-Chieh; Sabusap, Dexter Lyndon; Li, Jian-Jie; Hu, Shih-Cheng; Khodadadi, Jay M.; Jamshideasli, Dourna; Leggett, Graham
Abstract: Moisture contamination control has been adopted in many wafer handling and storage processes. In portable wafer carriers called front opening unified pods (FOUPs), the current industry-accepted methods of moisture control are gas purging and laminar air curtain (LAC). Both typically use purified clean dry air (CDA). In this study, we investigated five different methods of FOUP moisture control: conventional and diffuser-based purging, LAC, and combinations of each purging method with LAC. Two different scenarios of 100% and 75% FFU coverage area were examined. The FOUP was empty and its internal volume was exposed to a mock-up mini-environment (ME)–a process confinement device used in semiconductor fabs. Also, the LAC was mounted inside the ME above the FOUP opening. Smoke flow visualization, particle image velocimetry (PIV) and humidity measurement were performed in the FOUP median plane. Streamline flow patterns were obtained from the PIV results that can significantly enhance the evaluation of the moisture removal performance of different case studies. The findings showed that the combination of diffuser purge and LAC was the most resistant against external lateral moist air flow wherein it yielded the lowest average humidity. The findings could be beneficial for reducing waste and increasing product quality in semiconductor manufacturing. This can lead to significant reductions in energy usage and drastically reduce manufacturing costs.